Evaluating implementation research outcomes for a task-sharing mental health intervention: A systematic review of the Friendship Bench - John Patena; Deborah Adenikinju; Priyanka Lanka; Tania Hameed; Sumedha Kulkarni; Nana Osei-Tutu; Sophia Zuniga; Christina Ruan; Shivani Shenoy; Diksha Thakkar; Elizabeth Noble; Brian Angulo; et al. (Cambridge Prisms: Global Mental Health, 2025)
Common mental disorders (CMDs) are a leading cause of burden and disability globally. Approximately 75% of those living with CMDs reside in low- and middle-income countries (LMICs), and up to 90% of those needing mental health care do not receive it. The Friendship Bench is a task-sharing mental health intervention delivered by lay health workers (LHWs) that utilizes concepts of Problem-Solving Therapy. The aim of this systematic review is to identify and evaluate the barriers and facilitators to the implementation of research outcomes of the Friendship Bench and understand its systematic uptake to narrow the CMD treatment gap. We conducted a systematic review of articles that reported on the Friendship Bench in LMICs, CMDs, implementation research outcomes, and studies that utilized experimental, observational, or qualitative study designs. We identified articles using medical subject headings and keywords from APA PsycINFO, Cochrane, CINAHL, EMBASE, Global Health, OVID, PubMed/Medline, Science Direct, Web of Science, and Google Scholar in February 2023 and again in December 2023 to capture any additional articles. We screened 641 articles, and a total of 7 articles were included in the final analysis. All studies were conducted in Zimbabwe within the past 8 years, and across all the studies, all implementation research outcomes were reported. There is strong evidence that the Friendship Bench is acceptable, appropriate, and feasible to address the CMD treatment gap in Zimbabwe. Facilitators include that the Friendship Bench is culturally adaptable, utilizes trusted LHWs, and has relatively strong community and political buy-in. Conversely, barriers include a lack of a reliable mental health system, limitations in its ability to treat more serious mental conditions, and mental health stigma. There is an opportunity to explore the application of the Friendship Bench for CMDs in other countries and as a basis for novel task-sharing interventions for other health conditions.